Genetic and isotope analysis of a triple burial from medieval St. Peter's cemetery in Cölln/Berlin. (July 2022) - Rath, Kristin; Käßner, Alexandra; Melisch, Claudia; Powers, Natasha; Tichomirowa, Marion; Nagy, Marion; Friedrich, Ronny; Riege, Johanna; Rothe, Jessica
Abstract: The German capital Berlin originates from the two medieval settlements Berlin and Cölln on either side of the river Spree. Whereas Berlin is world famous, there is very little awareness of former Cölln. From 2007–2009, during excavations of the earliest cemetery of this forgotten medieval town; 3, 126 graves were discovered containing the remains of 3, 717 individuals. Amongst those graves was an unusual triple burial. This grave was exceptional due to the relative postures of the skeletons and their extensive facial injuries. Here we present genetic and isotope data for this grave. Genetic results confirmed all of them as biological male individuals and ruled out their biological kinship. Combining genetic ancestry information with strontium isotope data we furthermore determined that two of the men most likely originated from the Berlin-Brandenburg region, whereas a more distant origin of the third individual can be debated. Highlights: triple burial from medieval Berlin/Cölln reveals remains of three men in a crouching position and extensive injuries. genetic analysis indicates no close biological kinship between the individuals. genetic and isotope analyses of geographical origin assignes two individuals as local and one with a possible distant origin. data suggests that the shared grave arose from special circumstances of their death and the necessity of transport of the corpses to Berlin/Cölln.